Kepastian Hukum Terhadap Kasus Tumpang Tindih Pada Sebagian Bidang Tanah Yang Dikuasai oleh Dua Pihak Pemilik Sertipikat Hak Milik - Waluya, Carrissa Nurfaliza; Aksinuddin, Saim; Soleh, Yudi Prihartanto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Since the enactment of the Basic Agrarian Law in 1960, Indonesia has established a national legal framework, replacing the colonial system that lacked legal certainty for its people. The integration of customary law principles was key in the development of national land law, balancing aspects of communal and individual ownership. Property rights to land are clearly outlined in the Basic Agrarian Law, facilitating the transfer of ownership. However, there are still cases of overlapping land certificates. This study adopts a juridical-normative research method, analyzing legislation on land registration. The research aims to deepen understanding of legal regulation and dispute resolution, in the hope of improving legal certainty and protection in land ownership in Indonesia. Overlaps in land titles are emerging as a significant problem. Factors such as absenteeism during land boundary mapping, certificate forgery, and unclear inheritance division contribute to this overlap. Addressing this issue requires appropriate measures. Data correction, mediation, re-survey, annulment of legal products, or litigation are potential solutions.